Analyse De La Qualité Du Test Formatif Produit Par Les Professeurs Du Français Au Lycée À Semarang - Samudra, Hayyin Awwaliyya Tiyas; Astuti, Dwi (Program Studi Pendidikan Bahasa Prancis, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2020)
Chaque activitÃƒÂ© dÃ¢â‚¬â„¢enseignement doit toujours ÃƒÂªtre suivie de lÃ¢â‚¬â„¢ÃƒÂ©valuation. Selon la rÃƒÂ©daction, il y a deux types de test: le test standard et le test produit par le professeur. Le professeur de franÃƒÂ§ais doit faire attention aux rÃƒÂ¨gles de rÃƒÂ©daction pour faire le test. Cette recherche a le but de dÃƒÂ©crire la qualitÃƒÂ© du test formatif produit par les professeurs du franÃƒÂ§ais au lycÃƒÂ©e ÃƒÂ Semarang. Cette recherche est celle de descriptive qualitative. LÃ¢â‚¬â„¢objet de cette recherche est le test formatif de la classe X ÃƒÂ la rÃƒÂ©ponse courte, le test dÃ¢â‚¬â„¢association, le test ÃƒÂ la question ÃƒÂ choix multiple, et le test dÃ¢â‚¬â„¢essai produit par les professeurs du franÃƒÂ§ais ÃƒÂ Semarang. La source de donnÃƒÂ©e de cette recherche est la banque de test de quelque lycÃƒÂ©e ÃƒÂ Semarang. Cette recherche utilise la mÃƒÂ©thode de la documentation. AprÃƒÂ¨s la collection de donnÃƒÂ©e, cÃ¢â‚¬â„¢est lÃ¢â‚¬â„¢analyse selon les rÃƒÂ¨gles de rÃƒÂ©daction. Les rÃƒÂ©sultats montrent que la qualitÃƒÂ© du test formatif qui a ÃƒÂ©tÃƒÂ© fait par les professeurs du franÃƒÂ§ais au lycÃƒÂ©e ÃƒÂ Semarang est dans la catÃƒÂ©gorie bonne et le type du test qui a la meilleure qualitÃƒÂ© est le test ÃƒÂ la question ÃƒÂ choix multiple. Each teaching activity must always be followed by evaluation. There are two types of test: the standard test and the test produced by the teacher. The French teacher must pay attention to the writing rules to make the test. The purpose of this study is to determine the quality of formative test made by French teachers of Senior High School in Semarang. The approach used in this study is qualitative descriptive. The object of this study is formative test of class X of short answer test, matching test, multiple choice test, and essay made by French teachers of Senior High School in Semarang. The data source in this study is a bank of test that exists on each Senior High School in Semarang. The data collection method used is documentation. After data of formative test was collected, the data was analysed according to the rules of test production. The result showed that quality of formative test made by French teachers of Senior High School in Semarang is in the category good and the best quality test is the multiple choice test.